Utilization of vetiver grass containing metals as lignocellulosic raw materials for bioethanol production. Issue 8 (14th September 2021) - Restiawaty, Elvi; Dewi, Arinta; Budhi, Yogi Wibisono
Abstract: This study deals with bioethanol production from vetiver leaves contaminated with heavy metal ions, Al(iii ) and Ni(ii ). The effects of these ions on the growth of Neurospora intermedia and the production of bioethanol from vetiver leaves were investigated. The bioethanol production was carried out by a simultaneous saccharification and fermentation (SSF) method in submerged culture using N. intermedia . The SSF was operated micro-aerobically for 72 h. In order to enhance the bioethanol production, fermentation was anaerobically continued for more 72 h. The growth of N. intermedia was not affected by the presence of Al in a concentration range of 5–80 ppm. However, the growth rate of N. intermedia increased when the culture medium also contained 1 ppm Ni(ii ). The highest growth rate (0.031 h −1 ) was achieved when the culture medium contained 10 ppm Al(iii ) and 1 ppm Ni(ii ). The higher the Al(iii ) concentration contained in the culture medium, the lower the bioethanol yield. On the other hand, the presence of 1 ppm Ni(ii ) in the medium along with Al(iii ) increased the bioethanol yield. Vetiver leaves contaminated with 10 ppm Al(iii ) and 1 ppm Ni(ii ) can potentially be used as a substrate for bioethanol production.